SOLUTION OF ECONOMIC DISPATCH PROBLEM USING POLAR BEAR OPTIMIZATION ALGORITHM - Fayyaz, S; Ahmad, A; Imran Babar, M (univrcity of eloued, 2019)
Polar Bear optimization (PBO) algorithm is a newly developed meta-heuristic optimization algorithm that is inspired by the hunting behavior of polar bears in nature. PBO is a population based algorithm that combines three distinct features of optimization strategies to create a unique solution namely local search, global search and dynamic population. In this paper PBO algorithm is applied to solve economic dispatch problem of electrical power for both convex and non-convex systems. The proposed technique is tested on four IEEE benchmarks systems and the results obtained are compared with other techniques available in literature. Comparison of results obtained proved its success in reducing cost and computation time as compared to other techniques.
Article
Keywords: Polar Bear Optimization algorithm (PBO); Economic Dispatch of Electrical Power (EDEP); meta-heuristic; population based algorithms.